My ideal bookshelf - Mount, Jane; La Force, Thessaly (New York : Little, Brown and Company, 2012)
"The books that we choose to keep-let alone read-can say a lot about who we are and how we see ourselves. In THE IDEAL BOOKSHELF, dozens of leading cultural figures share the books that matter to them most-books that define their dreams and ambitions and in many cases helped them find their way in the world. With colorful and endearingly hand-rendered images of book spines by Jane Mount, and first-person commentary from all the contributors, this is a perfect gift for avid readers, writers, and all who have known the influence of a great book"--
Keywords: Books and reading -- Psychological aspects; Books and reading -- United States; Books in art; LITERARY COLLECTIONS / Essays; LANGUAGE ARTS & DISCIPLINES / Publishing; BIOGRAPHY & AUTOBIOGRAPHY / Editors, Journalists, Publishers